Adaptive Thresholding for Dark/Light States in Single Quantum Dot Blinking Fluorescence - Shchukina, A.L.; Eremchev, I.Yu (EPJ Web of conferences, 2015)
Quantum dots (QDs) are semiconductor nanocrystals with fluorescent properties depending on their composition, size, shape, etc. Many types of QDs manifest so-called blinking fluorescence, also typical for the majority of single quantum emitters (organic molecules, dielectric nanoparticles, etc.) [1,2]. Blinking of QDs is observed during cw-laser excitation: intervals of various intensities alternate in QD fluorescence. These are "dark" and "light" intervals. Various theories and hypotheses on the nature of QD dark states pursue to explain the subject [3].